2022
DOI: 10.3390/ijms23074058
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiling of WERI-RB1 and Etoposide-Resistant WERI-ETOR Reveals New Insights into Topoisomerase Inhibitor Resistance in Retinoblastoma

Abstract: Chemotherapy resistance is one of the reasons for eye loss in patients with retinoblastoma (RB). RB chemotherapy resistance has been studied in different cell culture models, such as WERI-RB1. In addition, chemotherapy-resistant RB subclones, such as the etoposide-resistant WERI-ETOR cell line have been established to improve the understanding of chemotherapy resistance in RB. The objective of this study was to characterize cell line models of an etoposide-sensitive WERI-RB1 and its etoposide-resistant subclon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In the past, several groups have explored the chemoresistance mechanisms in RB by developing drug-resistant clones from original RB cell lines and primary cell cultures established from enucleated specimens. 22 – 25 However, only a few gene expression studies have used either tumor or liquid biopsy samples from patients with RB. As EVs reflect the cell of origin at particular physiological and pathological conditions, they offer real-time monitoring of the tumor burden and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several groups have explored the chemoresistance mechanisms in RB by developing drug-resistant clones from original RB cell lines and primary cell cultures established from enucleated specimens. 22 – 25 However, only a few gene expression studies have used either tumor or liquid biopsy samples from patients with RB. As EVs reflect the cell of origin at particular physiological and pathological conditions, they offer real-time monitoring of the tumor burden and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NGF is involved in the regulation of TRPM8 activation, thereby controlling the influx of Ca 2+ , influencing the sensitivity of RB cells to etoposide [ 103 ]. Additionally, Vinodh Kakkassery et al determined that the pathways “retinoid metabolism and transport” and “sphingolipid de novo biosynthesis” are associated with etoposide resistance [ 104 ]. Furthermore, Jacqueline Reinhard et al demonstrated that components of the extracellular matrix play a crucial role in the development of chemotherapy resistance in RB [ 105 ].…”
Section: Epigenetics Of Rbmentioning
confidence: 99%
“… 80 Similar ML-based genetic analyses have revealed mechanisms for chemotherapy resistance in Rb including pathways related to retinoid metabolism and sphingolipid synthesis. 81 …”
Section: Studies In Rbmentioning
confidence: 99%